Resolution of tremor fluoxetine-induced in an elderly patient - Mastroianni, Patricia de Carvalho [UNESP]; Oliveira, Fernanda Marina de [UNESP]; Varallo, Fabiana Rossi [UNESP] (Sciencedomain International, 2015)
Aim: To report a possible case of tremor fluoxetine-induced treated as Parkinson’s disease in an elderly female patient noncompliant with the pharmacotherapy, with uncontrolled hypertension and using fluoxetine to treat depression. Presentation of Case: Patient complained of sleepiness in the morning, agitation, anxiety, insomnia and mental confusion. Her greatest concern was about bilateral hand tremors which, in her view became, worse after biperiden was prescribed. Therefore, she stopped taking it. The initial medication was: omeprazole, losartan, biperiden, fluoxetine, atenolol + chlorthalidone, acetylsalicylic acid, atorvastatin and diazepam. Pharmacotherapeutic follow up was performed in order to check the necessity, safety and effectiveness of treatment. Discussion: During the analysis of pharmacotherapy, the patient showed uncontrolled blood pressure and had difficulty complying with the treatment. Thus, in view of the complaints expressed by the patient, our first hypothesis was a possible serotonin syndrome related to fluoxetine use. We proposed a change in the fluoxetine regime and discontinuation of biperiden. As tremors persisted, we suggested the replacement of fluoxetine by sertraline, since a possible tremor fluoxetine-induced could explain the complaint. This approach solved the drug-related problem identified. Conclusion: Tremors reported by the patient was identified as an iatrogenic event related to fluoxetine, which was solved by management of serotonin-reuptake inhibitors.
Keywords: Fluoxetine; Sertraline; Serotonergic syndrome; Elderly|Primary health care; Pharmaceutical care